Mutations affecting the pattern of the larval cuticle in Drosophila melanogaster. - Nusslein-Volhard, C.; Wieschaus, E.; Kluding, H. (Wilhelm Roux's archives of developmental biology, 1984)
In a search for embryonic lethal mutants on the second chromosome ofDrosophila melanogaster, 5764 balanced lines isogenic for an ethyl methane sulfonate (EMS)-treatedcn bw sp chromosome were established. Of these lines, 4217 carried one or more newly induced lethal mutations corresponding to a total of 7600 lethal hits. Eggs were collected from lethal-bearing lines and unhatched embryos from the lines in which 25% or more of the embryos did not hatch (2843 lines) were dechorionated, fixed, cleared and scored under the compound microscope for abnormalities of the larval cuticle. A total of 272 mutants were isolated with phenotypes unequivocally distinguishable from wild-type embryos on the basis of the cuticular pattern. In complementation tests performed between mutants with similar phenotype, 48 loci were identified by more than one allele, the average being 5.4 alleles per locus. Complementation of all other mutants was shown by 13 mutants. Members of the complementation groups were mapped by recombination analysis. No clustering of loci with similar phenotypes was apparent. From the distribution of the allele frequencies and the rate of discovery of new loci, it was estimated that the 61 loci represent the majority of embryonic lethal loci on the second chromosome yielding phenotypes recognizable in the larval cuticle.